Effectiveness of intervention for aromatase inhibitor-associated musculoskeletal symptoms: A protocol for systematic review and meta-analysis. Issue 10 (11th March 2022) - Meng, Hui; Chen, Yuhan; Yu, Mingwei; Wang, Xiaomin
Abstract: Background: Aromatase inhibitor-associated musculoskeletal symptoms (AIMSS) are among the most common prominent side effects in patients using aromatase inhibitors (AIs) for breast cancer. Muscle and joint pain, morning stiffness, arthritis, and bone loss are common clinical symptoms in individuals. Traditional Chinese medicine (TCM) has been demonstrated to be useful in the treatment of AIMSS in previous investigations, although the sample sizes were limited, and systematic reviews were inadequate. The effectiveness and safety of TCM in the treatment of AIMSS will be investigated in this study. Methods: Randomized controlled trials from January 2010 to October 2021 were limited to English or Chinese. We searched PubMed, EMBASE, Cochrane Library, Web of Science, Medline, China Biomedical Database (CBM), China National Knowledge Infrastructure (CNKI), Wanfang database, and the VIP database. Two researchers reviewed the literature and retrieved the data independently. Review Manager V5.3.was used to conduct the statistical analysis. Results: This systematic review and meta-analysis presents the most recent data on the use of TCM to treat AIMSS and offers a scientifically sound foundation for therapeutic practice. Upon completion, the findings will be submitted to a peer-reviewed journal. Ethics and dissemination: As the systematic review protocol did not involve human subjects, ethical approval was not required. PROSPERO registration number: CRD42020192553.